Is the crime of self-money laundering punishable as an autonomous offense? (Universidad de San Andres Law Review, 2025)
This paper aims to analyze the criminalization of self-money laundering, following its inclusion as a criminal offense in 2011. There has been significant doctrinal debate on how to interpret the punishability of this crime not only in our country as the modification stems from the requirements of the international group FATF. Arguments opposing its punishability, often related to concealment, rely on the thesis of post-facto co-punished crimes, the prohibition of self-incrimination, the unfeasibility of requiring a different behavior, or the existence of a state of necessity that could justify the conduct. This study will examine and critique these objections, ultimately concluding that self-money laundering, as currently regulated, is punishable as an autonomous offense.
Keywords: money laundering; self-money laundering; punishability; co-punishment of post facto crimes; subsequent crime; prohibition of self-incrimination; non-existence of other conduct; state of necessity